Cinnamic acid derivatives in cosmetics: current use and future prospects - Gunia‐Krzyżak, A.; Słoczyńska, K.; Popiół, J.; Koczurkiewicz, P.; Marona, H.; Pękala, E. (International journal of cosmetic science, 2018)
Cinnamic acid derivatives are widely used in cosmetics and possess various functions. This group of compounds includes both naturally occurring and synthetic substances. On the basis of the Cosmetic Ingredient Database (CosIng) and available literature, this review summarizes their functions in cosmetics, including their physicochemical and biological properties as well as reported adverse effects. A perfuming function is typical of many derivatives of cinnamaldehyde, cinnamyl alcohol, dihydrocinnamyl alcohol and cinnamic acid itself; these substances are commonly used in cosmetics all over the world. Some of them show allergic and photoallergic potential, resulting in restrictions in maximum concentrations and/or a requirement to indicate the presence of some substances in the list of ingredients when their concentrations exceed certain fixed values in a cosmetic product. Another important function of cinnamic acid derivatives in cosmetics is UV protection. Ester derivatives such as ethylhexyl methoxycinnamate (octinoxate), isoamyl p‐methoxycinnamte (amiloxiate), octocrylene and cinoxate are used in cosmetics all over the world as UV filters. However, their maximum concentrations in cosmetic products are restricted due to their adverse effects, which include contact and a photocontact allergies, phototoxic contact dermatitis, contact dermatitis, estrogenic modulation and generation of reactive oxygen species. Other rarely utilized functions of cinnamic acid derivatives are as an antioxidant, in skin conditioning, hair conditioning, as a tonic and in antimicrobial activities. Moreover, some currently investigated natural and synthetic derivatives of cinnamic acid have shown skin lightening and anti‐ageing properties. Some of them may become new cosmetic ingredients in the future. In particular, 4‐hydroxycinnamic acid, which is currently indexed as a skin‐conditioning cosmetics ingredient, has been widely tested in vitro and in vivo as a new drug candidate for the treatment of hyperpigmentation. Résumé Les dérivés de l'acide cinnamique sont largement utilisés dans les cosmétiques et ils possèdent diverses fonctions. Ce groupe de composés comprend des substances naturelles et synthétiques. Fondée sur la base de données CosmeticIngredient (CosIng) et sur la littérature disponible, cette revue résume leurs fonctions dans les cosmétiques, avec leurs propriétés physico‐chimiques et biologiques ainsi que leurs effets indésirables rapportés. Une fonction parfumante est typique de nombreux dérivés du cinnamaldéhyde, de l'alcool cinnamylique, de l'alcool dihydrocinnamylique et de l'acide cinnamique lui‐même; ces substances sont couramment utilisées dans les cosmétiques, partout dans le monde. Certaines d'entre elles présentent un potentiel allergique et photoallergique, entraînant des restrictions dans les concentrations maximales et/ou une obligation d'indiquer la présence de certaines substances dans la liste des ingrédients lorsque leurs concentrations dépassent certaines valeurs fixes dans un produit cosmétique. Une autre fonction importante des dérivés de l'acide cinnamique dans les cosmétiques est la protection contre les UV. Des dérivés esters tels que l’éthylhexyle p‐méthoxycinnamate (octinoxate), l'isoamyle p‐méthoxycinnamate (amiloxiate), l'octocrylène et le cinoxate sont utilisés dans les cosmétiques du monde entier comme filtres UV. Cependant, leurs concentrations maximales dans les produits cosmétiques sont limitées en raison de leurs effets indésirables, qui comprennent les allergies de contact et de photocontact, la dermatite phototoxique de contact, la dermatite de contact, la modulation œstrogénique et la génération de dérivés réactifs de l'oxygène. D'autres utilisations plus rares des dérivés de l'acide cinnamique sont basées sur leurs fonctions antioxydantes (soins de la peau, conditionneurs capillaires, toniques) et leur activité antimicrobienne. De plus, certains dérivés naturels et synthétiques de l'acide cinnamique actuellement étudiés ont montré des propriétés éclaircissantes et anti‐âge. Certains d'entre eux pourraient devenir de nouveaux ingrédients des cosmétiques de l'avenir. En particulier, l'acide 4‐hydroxycinnamique, actuellement répertorié comme ingrédient cosmétique pour le conditionnement de la peau, a été largement testé in vitro et in vivo comme nouveau médicament candidat pour le traitement de l'hyperpigmentation.